IMPORTANCE OF THE PERFORMANCE ANALYSIS (IPA) AND CUSTOMER SATISFACTION FOR DETERMINING THE SERVICE STRATEGIES THROUGH THE SERVQUAL MODEL APPROACH - ., Kasnadi; Indrayani, Rina (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2019)
The culinary industry in Bandung is very numerous and varied. So it is necessary to match the level of importance of service products according to costumers and the level of performance that a restaurant has given. This study is to determine the level of customer satisfaction on the quality of restaurant services and to provide suggestions on which service products that become and to determine service strategies. The method used is the method of Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results of processing data with the IPA method obtained 6 service products that need attention. The results of data processing from the CSI method show the level of customer satisfaction of 0.682%. Although it meets or is within the criteria of satisfaction, it needs a service strategy by making improvements to product services by providing a clear standard of service time to implement a culture of discipline, maximizing employee training to improve the ability of employees to handle customers, and conducting promotions in the form of price discounts at certain times, and maintaining good relations with suppliers.